Peningkatan Hasil Belajar dalam Pembelajaran Tematik Terpadu menggunakan Model TSTS di Kelas IV SD - Monica, Adella; Zuardi, Zuardi (Universitas Negeri Padang, 2022)
This study aims to describe the improvement of student learning outcomes in Integrated thematic Learning using Two Stay Two Stray model in class IV SDN 05 Koto Tangah Kabupaten Agam. This research used a qualitative and quantitative approach. This type of research i.e. Research Action class (PTK). The subject of research is the grade IV SDN 05 Koto Tangah KabupatenAgam Feed as many as 16 students. Research conducted two cycles. The design of the research include, (1) planning, (2) implementation, (3) and (4) observation of the reflection. The results showed an increase in: a) the RPP cycle I 83,33(B)% ,Cycle II 94,44% (SB) b) implementation on aspect of teacher cycle I 85,93% (B), a cycle II 96,87% (SB) c) Implementation on aspect students cycle I 84,37% (B) and Cycle II 93,75% (SB) d) student learning outcomes Cycle I 73,67 (B), cycle II 86,64 (A). Thus the model of Two Stay Two Stray can improve the learning results of integrated thematic grade IV SDN 05 Koto Tangah Kabupaten Agam.